Location via proxy:   [ UP ]  
[Report a bug]   [Manage cookies]                

Check Out The Truth Table To Convince Yourself of This

Download as pdf or txt
Download as pdf or txt
You are on page 1of 3

Boolean algebra notes

Some useful Boolean logic formulae


Note the use of the notation a' to indicate (NOT a)
a+0=a

a.0 = 0

a+1=1

a.1 = a

a+a=a

a.a = a

a + a' = 1

a.a' = 0

From these basic identities, we can derive equalities involving two variables, e.g.
a.b + a.b' = a.(b + b') = a
So: a.b + a.b' = a (check out the truth table to convince yourself of this)
Also: a + a.b = a.(1 + b) = a.1 = a
So: a + a.b = a (check out the truth table to convince yourself of this)
Also: a + a'.b = a + a.b + a.b (using a + a.b = a)
= a + (a + a).b
=a+b
So: a + a'.b = a + b (check out the truth table to convince yourself of this)

Summarizing 2-variable identities:


a.b + a.b' = a

a + a.b = a

a + a'.b = a + b

de Morgan's Law: (you can find the proof in any discrete math site)
(a + b)' = a'.b'
(a.b)' = a' + b'

Worked example

Represent the following truth table as a boolean expression:


a

First, we build the and expressions that correspond to all the lines that give an
output = 1, and connect them all with or operators:
f=

a'.b'.c.d'
+ a'.b'.c.d
+ a'.b.c.d'
+ a'.b.c.d
+ a.b'.c'.d
+ a.b'.c.d
+ a.b.c'.d
+ a.b.c.d'
+ a.b.c.d

Remembering that we can or an extra term a.b.c.d without altering the value
(since x + x = x), we can then group these terms as follows:
f = (a'.b'.c.d' + a'.b'.c.d)
+ (a'.b.c.d' + a'.b.c.d)
+ (a.b'.c'.d + a.b'.c.d)
+ (a.b.c'.d + a.b.c.d)
+ (a.b.c.d' + a.b.c.d)
Noting that (x.y + x.y') = x, we have:
a'.b'.c.d' + a'.b'.c.d = a'.b'.c
and similarly for each of the pairs shown. So:
f = a'.b'.c + a'.b.c + a.b'.d + a.b.d + a.b.c
Pairing terms again ("re-using" the term a'.b.c):
f = (a'.b'.c + a'.b.c) + (a.b'.d + a.b.d) + (a'.b.c + a.b.c)
and noting again that
We finally get:
f = a'.c + a.d + b.c

a'.b'.c + a'.b.c = a'.c

etc.

You might also like